A preparation method of a degradable air column bag and an air column bag
By combining chitosan grafted bialdehyde starch with sodium alginate solution and other raw materials, modified alginate fibers are formed, which solves the problem of easy damage to the gas column bag under external impact, and achieves the excellent impact resistance of the gas column bag and Good degradability significantly reduces the frequency of damage.
Patent Information
- Application Number
- CN202311043974.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-08-17
AI Technical Summary
The existing biodegradable gas column bags are easily damaged by external impact during transportation and storage, and lack sufficient impact resistance.
The combination of chitosan grafted bisaldehyde starch and sodium alginate solution and other raw materials is used to form modified alginate fibers through catalytic reaction, and combined with degradable resins and plasticizers, gas column bags with excellent impact resistance are prepared.
It significantly improves the resistance of the air column bag to external impact, reduces the frequency of damage, and maintains good degradation and is environmentally friendly.
Smart Images

Figure CN116904008B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of air column bags, and more specifically, to a preparation method of a degradable air column bag and the air column bag. Background Art
[0002] Air column bags, also known as cushioning air column bags, inflatable bags, bubble column bags, and columnar inflatable bags, are new packaging materials filled with natural air. Through comprehensive air column cushioning protection, the product transportation loss rate is reduced to a minimum. Air column bags have a wide range of applications and are designed to protect a series of products during transportation, as well as the storage environment after the transportation cycle is completed.
[0003] For example, the patent application with the publication number CN115746523A discloses a new material air column bag with strong degradation ability and its preparation method. The new material air column bag with strong degradation ability is made of degradable plastic, and the degradable plastic is composed of the following raw materials in parts by weight: 100-140 parts of polylactic acid, 6-10 parts of polyvinyl alcohol, 3-5 parts of nucleating agent, 1-3 parts of coupling agent, 1-3 parts of plasticizer, 1-1.4 parts of photocatalyst, and 7-11 parts of auxiliary components, wherein the auxiliary components include nutritional components, decomposition components that promote the decomposition of nutritional components, and toughening components, and the weight ratio of the nutritional components, decomposition components, and toughening components is (3-5): (2-4): 2. The above-mentioned air column bag can be used for packaging of articles. Although the above-mentioned air column bag has good degradation ability and is environmentally friendly, after the air column bag is packaged with articles, it will be impacted by external forces during transportation and storage, and the air column bag is often damaged. Summary of the invention
[0004] The present application provides a method for preparing a degradable air column bag and an air column bag. The obtained air column bag not only has good degradability and is environmentally friendly, but also has excellent impact resistance and good toughness, and can significantly improve the phenomenon of damage to the air column bag after being subjected to external force impact.
[0005] In the first aspect, the present application provides a method for preparing a degradable air column bag using the following technical solution:
[0006] A method for preparing a degradable air column bag comprises the following steps:
[0007] Preparation of masterbatch: Add the filler modified by coupling agent and excess dialdehyde starch into chitosan solution, and heat the reaction under the action of catalyst to obtain masterbatch;
[0008] Preparation of modified alginate fiber: Ultrasonic mixing of sodium alginate solution and masterbatch at a mass ratio of 3:(0.8-2) to form a spinning solution, and spinning the spinning solution to obtain modified alginate fiber;
[0009] Preparation of degradable masterbatch: Degradable resin, modified alginate fiber, plasticizer, lubricant and antioxidant are extruded and granulated to obtain degradable masterbatch.
[0010] Preparation of air column bags: The biodegradable masterbatch is blown into film, and then heat-sealed and cut to form air column bags.
[0011] Furthermore, the preparation step of the chitosan solution is specifically as follows: dissolving chitosan in a dilute acid solution and stirring evenly to obtain the chitosan solution.
[0012] As a preferred embodiment of chitosan, it is more preferred to use chitosan with a deacetylation degree of more than 80%.
[0013] Furthermore, the dilute acid solution is one of oxalic acid solution and acetic acid solution, and more preferably acetic acid solution, and its mass concentration is more preferably 2-4%.
[0014] The catalyst may be an acid catalyst or a base catalyst, and is preferably acetic acid.
[0015] The present application adopts chitosan grafted with dialdehyde starch. The chitosan solution contains certain amino groups, which can react with the aldehyde groups contained in the dialdehyde starch to form a Schiff base reaction, thereby grafting the dialdehyde starch onto the chitosan, and compounding and reacting with the filler modified by the coupling agent to obtain a masterbatch with good impact resistance. The masterbatch is compounded with the sodium alginate solution in a specific ratio to form a spinning solution. Since the dialdehyde starch in the masterbatch is excessive, the dialdehyde starch can be further used as a cross-linking agent to facilitate the spinning solution to form modified alginate fibers through spinning. The modified alginate fibers obtained not only have excellent toughness, but also have good compatibility with raw materials such as degradable resins, promote uniform dispersion of the system, so that the final air column bag not only has good degradability and is environmentally friendly, but also has excellent impact resistance and good toughness, which can significantly reduce the phenomenon of damage to the air column bag after being impacted by external forces.
[0016] The air column bag obtained by compounding raw material components such as dialdehyde starch, chitosan solution, sodium alginate solution, and degradable resin has good degradability, is environmentally friendly, and greatly alleviates environmental pressure.
[0017] Preferably, in the preparation of the masterbatch, the amounts of the components used are as follows, in parts by weight: 15-30 parts of chitosan solution, 3-7 parts of filler, 8-16 parts of dialdehyde starch, and 0.3-0.8 parts of catalyst.
[0018] Furthermore, the filler modified by the coupling agent is specifically: the filler is ball-milled for 0.5-1h with the coupling agent as the medium to improve the apparent performance of the filler, increase the surface activity of the filler, and promote the compatibility and dispersibility between the raw material components.
[0019] The further coupling agent is selected from one of a silane coupling agent and a titanate coupling agent.
[0020] As a further preferred embodiment of the coupling agent, it is better to select a silane coupling agent as the coupling agent.
[0021] By adopting the above technical solution, the dosage relationship between the raw material components in the masterbatch is optimized, the chitosan grafting rate is increased, and the impact resistance of the masterbatch is further improved.
[0022] Preferably, in the preparation of the degradable masterbatch, the amounts of components used are as follows, in parts by weight, 60-80 parts of degradable resin, 20-35 parts of modified alginate fiber, 1-3 parts of plasticizer, 0.5-2 parts of lubricant, and 1-3 parts of antioxidant.
[0023] Furthermore, the antioxidant is preferably antioxidant 1010 or antioxidant 1076.
[0024] Furthermore, the lubricant is one of stearate and fatty acid amide. The lubricant can be calcium stearate or zinc stearate.
[0025] By adopting the above technical scheme, the dosage relationship between the degradable resin, modified alginate fiber, plasticizer, lubricant and antioxidant is optimized to ensure that the air column bag has excellent degradability, is environmentally friendly, and at the same time improves the impact resistance of the air column bag and improves the phenomenon of damage of the air column bag after being subjected to external force impact.
[0026] Preferably, the mass concentration of the chitosan solution is 8-15%.
[0027] Preferably, the mass concentration of the sodium alginate solution is 5-12%.
[0028] By adopting the above technical solution, the mass concentration of the chitosan solution and the mass concentration of the sodium alginate solution are further optimized, and the comprehensive performance of the masterbatch and the degradable masterbatch is assisted to improve, thereby improving the product quality of the air column bag.
[0029] Preferably, the filler comprises calcium carbonate and / or mica powder.
[0030] Furthermore, the filler may be calcium carbonate, mica powder, or a combination of calcium carbonate and mica powder.
[0031] The fillers are preferably nano-scale calcium carbonate and mica powder, which can give the masterbatch excellent impact resistance and toughness, and improve the phenomenon of the air column bag being damaged after being impacted by external forces.
[0032] Preferably, the degradable resin includes one or more of polylactic acid resin, polycarbonate resin, and polybutylene succinate. The degradable resin may be polylactic acid resin, a compound of polycarbonate resin and polybutylene succinate, or a compound of polylactic acid resin and polycarbonate resin.
[0033] Preferably, the plasticizer includes one of dibutyl maleate, dibutyl phthalate, and epoxidized soybean oil.
[0034] By adopting the above technical scheme, polylactic acid resin, polycarbonate resin and polybutylene succinate all have good degradability and are environmentally friendly. Under the modification of the degradable masterbatch, the toughness of the air column bag can be effectively improved and the impact resistance of the product can be improved.
[0035] Selecting a suitable plasticizer can weaken the interaction between polymer molecules, increase the plasticity of the resin raw material, improve its fluidity during molding, and improve the processing performance of the resin raw material.
[0036] Preferably, during the preparation of the masterbatch, the temperature is raised to 60-75° C. and reacted for 1-2 hours.
[0037] Adjusting the reaction temperature is beneficial to the positive reaction and promotes the formation of masterbatch.
[0038] In the second aspect, the present application provides a degradable air column bag, which adopts the following technical solution:
[0039] A degradable air column bag is prepared by the above-mentioned preparation method of the degradable air column bag.
[0040] By adopting the above technical solution, the obtained air column bag not only has good degradability and is environmentally friendly, but also has excellent impact resistance and good toughness, and can significantly improve the phenomenon of damage to the air column bag after being subjected to external force impact.
[0041] In summary, this application has the following beneficial effects:
[0042] Chitosan is grafted with dialdehyde starch. The chitosan solution contains certain amino groups, which can react with the aldehyde groups contained in dialdehyde starch to form a Schiff base reaction. The dialdehyde starch is grafted onto chitosan and compounded with a filler modified by a coupling agent to obtain a masterbatch with good toughness. The masterbatch is compounded with a sodium alginate solution in a specific ratio to form a spinning solution, which is then spun to form modified alginate fibers. The modified alginate fibers obtained not only have excellent toughness, but also have good compatibility with raw materials such as degradable resins, and promote uniform dispersion of the system, so that the final air column bag not only has good degradability and is environmentally friendly, but also has excellent impact resistance and good toughness, which can significantly reduce the phenomenon of damage to the air column bag after being impacted by external forces. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a flowchart of the preparation process of the degradable air column bag of this application. DETAILED DESCRIPTION
[0044] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0045] Example
[0046] Example 1
[0047] A method for preparing a degradable air column bag comprises the following steps:
[0048] Masterbatch preparation:
[0049] Using silane coupling agent as medium, the filler is ball-milled for 0.5 h to obtain a filler modified by coupling agent;
[0050] Dissolve chitosan in acetic acid solution and stir evenly to obtain a chitosan solution with a mass concentration of 15%;
[0051] The filler modified by the coupling agent and dialdehyde starch are added into the chitosan solution, and the temperature is raised to 60° C. under the action of a catalyst to react for 1 hour to obtain a masterbatch;
[0052] Specifically, the filler is nano-scale calcium carbonate; 7 parts of filler, 8 parts of dialdehyde starch, and 15 parts of chitosan solution;
[0053] Preparation of modified alginate fiber: a sodium alginate solution with a mass concentration of 5% and a masterbatch are ultrasonically mixed at a mass ratio of 3:2 to form a spinning solution, and the spinning solution is spun to obtain modified alginate fiber;
[0054] Preparation of degradable masterbatch: 60 parts of polylactic acid resin, 20 parts of modified alginate fiber, 1 part of dibutyl maleate, 0.5 parts of zinc stearate and 1 part of antioxidant 1010 are extruded and granulated to obtain a degradable masterbatch;
[0055] Preparation of air column bags: The biodegradable masterbatch is blown into film, and then heat-sealed and cut to form air column bags.
[0056] Example 2
[0057] A method for preparing a degradable air column bag comprises the following steps:
[0058] Masterbatch preparation:
[0059] The filler was ball-milled for 1 h using a titanate coupling agent as a medium to obtain a coupling agent-modified filler;
[0060] Dissolve chitosan in oxalic acid solution and stir evenly to obtain a chitosan solution with a mass concentration of 8%;
[0061] The filler modified by the coupling agent and dialdehyde starch are added to the chitosan solution, and the temperature is raised to 75°C for reaction for 0.5h under the action of a catalyst to obtain a masterbatch;
[0062] Specifically, the filler is nano-mica powder; 3 parts of filler, 16 parts of dialdehyde starch, and 30 parts of chitosan solution;
[0063] Preparation of modified alginate fiber: a sodium alginate solution with a mass concentration of 12% and a masterbatch are ultrasonically mixed at a mass ratio of 3:0.8 to form a spinning solution, and the spinning solution is spun to obtain modified alginate fiber;
[0064] Preparation of degradable masterbatch: 80 parts of polybutylene succinate, 35 parts of modified alginate fiber, 3 parts of plasticizer, 2 parts of fatty acid amide and 3 parts of antioxidant 1076 are extruded and granulated to obtain a degradable masterbatch;
[0065] Preparation of air column bags: The biodegradable masterbatch is blown into film, and then heat-sealed and cut to form air column bags.
[0066] Example 3
[0067] The difference from Example 1 is that the masterbatch is prepared as follows:
[0068] Dissolve chitosan in acetic acid solution and stir evenly to obtain a chitosan solution with a mass concentration of 12%;
[0069] The coupling agent-modified filler and dialdehyde starch were added to the chitosan solution, and the temperature was raised to 70°C for reaction for 0.5h under the action of a catalyst to obtain a masterbatch;
[0070] Specifically, the filler is 1 part of nano-scale calcium carbonate and 1 part of mica powder; 12 parts of dialdehyde starch and 22 parts of chitosan solution;
[0071] The rest are the same as in Example 1.
[0072] Example 4
[0073] The difference from Example 3 is that in the preparation of the masterbatch, the mass concentration of the chitosan solution is 5%, the mass concentration of the sodium alginate solution is 15%, and the filler is 2 parts of kaolin;
[0074] The rest is the same as Example 3.
[0075] Example 5
[0076] The difference from Example 3 is that the modified alginate fiber is prepared by ultrasonically mixing a sodium alginate solution with a mass concentration of 9% and a masterbatch at a mass ratio of 3:1.6 to form a spinning solution, and spinning the spinning solution to obtain the modified alginate fiber;
[0077] The rest is the same as Example 3.
[0078] Example 6
[0079] The difference from Example 5 is that the degradable masterbatch is prepared by extruding and granulating 40 parts of polylactic acid resin, 30 parts of polycarbonate, 30 parts of modified alginate fiber, 1.5 parts of epoxy soybean oil, 1 part of zinc stearate and 1.8 parts of antioxidant 1010 to obtain a degradable masterbatch;
[0080] The rest are the same as in Example 5.
[0081] Example 7
[0082] The difference from Example 6 is that the degradable masterbatch is prepared by extruding and granulating 40 parts of polybutylene succinate, 40 parts of polycarbonate, 18 parts of modified alginate fiber, 4 parts of epoxy soybean oil, 1 part of zinc stearate and 0.4 parts of antioxidant 1010 to obtain a degradable masterbatch;
[0083] The rest are the same as in Example 6.
[0084] Comparative Example
[0085] Comparative Example 1
[0086] The difference from Example 6 is that no dialdehyde starch is added in the preparation of the masterbatch, and the rest is the same as Example 6.
[0087] Comparative Example 2
[0088] The difference from Example 6 is that in the preparation of the masterbatch, an equal amount of dialdehyde starch is replaced by cassava starch, and the rest is the same as Example 6.
[0089] Comparative Example 3
[0090] The difference from Example 6 is that in the preparation of the modified alginate fiber, the mass ratio of the sodium alginate solution to the masterbatch is 0.8:1.5; the rest is the same as Example 6.
[0091] Comparative Example 4
[0092] The difference from Example 6 is that unmodified commercially available ordinary alginate fibers are selected, and the rest are the same as Example 6.
[0093] Performance testing
[0094] The samples obtained in Examples 1-7 and Comparative Examples 1-4 were correctly selected from each film to be tested and cut into 30*30 cm square samples, 30 pieces in each group. The films were free of bubbles, wrinkles, creases and other obvious defects. According to GB / T 9639.1-2008 "Test method for impact resistance of plastic films and sheets - free falling dart method", the impact resistance test was carried out. The dart drop height was 80 cm, the dart drop weight was 300 g, the total number of damaged samples was recorded, and the dart drop weight was adjusted to record the minimum dart drop mass when the sample was damaged. The results are recorded in Table 1.
[0095] Table 1
[0096]
[0097]
[0098] In combination with Examples 1-7 and Table 1, it can be seen that the use of the specific components and preparation methods of the present application can effectively increase the minimum dart weight when the product is just broken, and after withstanding the impact of a dart weight of 300g, the amount of breakage is low, which can significantly reduce the phenomenon of breakage of the air column bag after being impacted by external forces, and the obtained air column bag has excellent impact resistance.
[0099] Combining Example 6 and Comparative Examples 1-2 and Table 1, it can be seen that no dialdehyde starch is added in Comparative Example 1, and cassava starch is used in Comparative Example 2. When the air column bags prepared in Comparative Examples 1 and 2 are subjected to external force impact, the minimum dart weight when broken is significantly reduced, and after being impacted by a dart weight of 300g, the amount of breakage is significantly increased, and the impact resistance of the air column bag is significantly reduced. This is because the chitosan solution used contains a certain amino group, which can react with the aldehyde group contained in the dialdehyde starch to produce a Schiff base reaction, graft the dialdehyde starch onto the chitosan, and react with the filler modified by the coupling agent to obtain a masterbatch with good impact resistance, thereby improving the quality of the air column bag.
[0100] Combining Example 6 and Comparative Examples 3-4, it can be seen that the compounding ratio of the masterbatch and the sodium alginate solution in Comparative Example 3 is unbalanced, and the formed spinning solution has a significant effect on the quality of the modified alginate fiber obtained during the spinning process, resulting in poor quality of the air column bag. In Comparative Example 4, unmodified commercially available ordinary alginate fiber is selected, and the obtained air column bag is subjected to external force impact. The minimum dart drop weight when the air column bag is damaged decreases, and after being impacted by a dart drop weight of 300g, the damage amount is significantly increased, and the impact resistance of the air column bag is significantly reduced. It can be seen that only by using the masterbatch of the present application and the sodium alginate solution to form a spinning solution in a specific ratio, and then using the excess dialdehyde starch in the masterbatch as a cross-linking agent, the formed spinning solution after spinning forms a modified alginate fiber that not only has excellent toughness, but also has good compatibility with raw materials such as degradable resins, promotes uniform dispersion of the system, and makes the final air column bag have excellent impact resistance, which can significantly reduce the phenomenon of damage to the air column bag after being subjected to external force impact.
[0101] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a degradable air column bag, characterized in that: The following steps are involved: Preparation of masterbatch: adding a coupling agent-modified filler and an excess of dialdehyde starch to a chitosan solution, heating the mixture under the action of a catalyst to obtain a masterbatch; in the preparation of the masterbatch, the amounts of the components used are as follows, in parts by weight: 15-30 parts of chitosan solution, 0.1-0.3 parts of coupling agent, 3-7 parts of filler, 8-16 parts of dialdehyde starch, and 0.3-0.8 parts of catalyst; Preparation of modified alginate fiber: Ultrasonic mixing of sodium alginate solution and masterbatch at a mass ratio of 3:(0.8-2) to form a spinning solution, and spinning the spinning solution to obtain modified alginate fiber; Preparation of degradable masterbatch: Degradable resin, modified alginate fiber, plasticizer, lubricant and antioxidant are extruded and granulated to obtain degradable masterbatch. In the preparation of the degradable masterbatch, the amounts of the components used are as follows, in parts by weight, 60-80 parts of degradable resin, 20-35 parts of modified alginate fiber, 1-3 parts of plasticizer, 0.5-2 parts of lubricant, and 1-3 parts of antioxidant; the degradable resin includes one or more of polylactic acid resin, polycarbonate resin, and polybutylene succinate; Preparation of air column bags: The biodegradable masterbatch is blown into film, and then heat-sealed and cut to form air column bags.
2. The method for preparing the degradable air column bag according to claim 1, characterized in that: The mass concentration of the chitosan solution is 8-15%.
3. The method for preparing the degradable air column bag according to claim 1, characterized in that: The mass concentration of the sodium alginate solution is 5-12%.
4. The method for preparing the degradable air column bag according to claim 1, characterized in that: The filler includes calcium carbonate and / or mica powder.
5. The method for preparing the degradable air column bag according to claim 1, characterized in that: The plasticizer includes one of dibutyl maleate, dibutyl phthalate and epoxidized soybean oil.
6. The method for preparing the degradable air column bag according to claim 1, characterized in that: During the preparation of the masterbatch, the temperature is raised to 60-75° C. and reacted for 1-2 hours.
7. A degradable air column bag, characterized in that: The degradable air column bag is prepared by the preparation method of any one of claims 1 to 6.
